Cydalima perspectalis in Poland—8 Years of Invasion against the Background of Three Other Invasive Species - Paweł K. Bereś; Patrycja Ziętara; Mirosław Nakonieczny; Łukasz Kontowski; Michał Grzbiela; Maria Augustyniak (Diversity, 2021)
The box tree moth (Cydalima perspectalis) origins from East Asia. In Europe, it was recorded for the first time in 2007, and in Poland in 2012. By the end of 2020, it was found all over Poland. There are no published data on the range of C. perspectalis occurrence in Poland because it is not a quarantine pest in the European Union and is not subject to official monitoring. Data collected in 2018–2020 via a website dedicated to monitoring, for the first time, illustrate the current range and its largest concentrations in southern and central Poland. The monitoring confirmed that the main directions of the invasion are related to the main communication routes of Poland (south-north) and are of a long-distance character. The dispersal pattern corresponds to the model developed for Cameraria ohridella: a stratified dispersal model that considers long-distance road/rail transport. The second important factor contributing to the invasion of C. perspectalis are large human communities enabling rapid local dispersion (a diffusion model). Comparing its invasion with the monitoring data from 2007–2013 of two other invasive pests of Poland: Ostrinia nubilalis and Diabrotica virgifera, shows that a diffusion model best describes the spatial spread of these pests only to uninhabited neighboring areas.